E-Government Media Informasi Alat Kelengkapan Dewan Provinsi Bali dan Media Diskusi Berbasis Website - Sugiartawan, Putu; Rustina, I Dewa Ketut Rai; Saleh Insani, Rachmat Wahid (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2018)
The development of technology and information at this time is very fast, one of which is the internet. The ease of digging information through a website encourages state institutions to use the website as a medium of information to the public. The purpose of this research is to build and design E-Gov media information in the DPRD of the Province of Bali which is used as a medium of information and discussion that can be utilized by the community and the council. Website content only displays information about the board such as board fittings with the following sub-sections; Leadership of the Board, Commissions, Bamus, Banggar, Baleg, Honorary Board. As well as allowing website visitors to be able to express aspirations to the board